2016
DOI: 10.1186/s13046-016-0447-3
|View full text |Cite|
|
Sign up to set email alerts
|

A panel of four genes accurately differentiates benign from malignant thyroid nodules

Abstract: BackgroundClinicians are confronted with an increasing number of patients with thyroid nodules. Reliable preoperative diagnosis of thyroid nodules remains a challenge because of inconclusive cytological examination of fine-needle aspiration biopsies. Although molecular analysis of thyroid tissue has shown promise as a diagnostic tool in recent years, it has not been successfully applied in routine clinical use, particularly in Chinese patients.MethodsWhole-transcriptome sequencing of 19 primary papillary thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…With the help of sequencing technology, we have been revealed whole transcriptome bioinformation of 19 pairs PTC samples and its adjacent normal thyroid tissues . The results showed that SCARA5 might act as a vital anti‐tumour gene in the PTC.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of sequencing technology, we have been revealed whole transcriptome bioinformation of 19 pairs PTC samples and its adjacent normal thyroid tissues . The results showed that SCARA5 might act as a vital anti‐tumour gene in the PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation sequencing has been widely used in the study of the gene expression variations and cancer molecular mechanism. In our previous study, we selected 19 matched pairs of thyroid carcinoma tissues and nearby non‐cancerous tissues and the outcomes revealed that GAP43 expression was overexpressed in tumour tissues. This finding suggested GAP43 may have a possible role as an oncogene in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we have conducted next‐generation of 19 pairs of PTC tissues and adjacent normal thyroid tissue . After evaluating all the information, we identified that growth‐associated protein 43 (GAP43), a gene encoding an axonal membrane protein, as an oncogene promotes PTC tumorigenesis and tumour progression . As for the normal function of this protein, it is normally expressed in neuronal somata, axons and growth cones during pre‐ and early postnatal development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other technologies, including gene and protein expression signatures [210][211][212][213][214], have also been developed to help to decipher the code that differentiates benign and cancerous molecular anomalies. Intriguingly, there are models that predict (with up to 90% accuracy) the pattern of epigenetic changes found on circulating DNA in the bloodstream that imply malignancy versus those that do not [215].…”
Section: Confounding the Holy Grail-early Detection Of Cancer With Blmentioning
confidence: 99%